SAT0415 Effects of Intra-Articular Clodronate in the Treatment of Knee Osteoarthritis: Results of A Double-Blind, Randomised Placebo-Controlled Trial. (10th June 2014) - Orsolini, G.; Idolazzi, L.; Rossini, M.; Viapiana, O.; Fracassi, E.; Povino, M.; Risoli, M.; Gatti, D.; Adami, S.
Abstract : Background: Recently data strengthens the concept that treatment with bisphosphonates may be associated with beneficial symptomatic effects and perhaps structural benefits in people with osteoarthritis. Objectives: Aim of this study was to evaluate the efficacy and tolerability of intra-articular (IA) clodronate, compared to saline solution, in patients with symptomatic knee osteoarthritis (KOA). Methods: In this double blind phase 3 randomized clinical trial patients were randomized to receive once weekly IA injection of 2 mg clodronate or placebo for 4 weeks with 14 weeks of follow-up. The primary objective was the sum of spontaneous, on passive movement and at digital pressing pain relief assessed by visual analogue score (VAS) of 0-100. Improving in Western Ontario MacMaster (WOMAC) scale, Lequesne Index, consumption of acetaminophen, and physician or patient overall judgment were secondary objectives. Results: Study population included 80 patients, 67 women and 13 men aged 66±6 (SD) years. A significant improvement for all efficacy parameters was observed at all-time points in both groups. A significant difference in favor to clodronate in VAS for pain was observed 3 and 5 weeks after the last injection. The improvements in Lequesne index, global KOA evaluation from both patients and investigators, and the WOMAC pain subscale were significantly greater in clodronate group 3-5 weeks after the last injection. The proportion of patients that did not require acetaminophen was significantly greater in the clodronate group. Conclusions: IA 2 mg clodronate is safe and is associated with small and transient symptomatic and functional benefits in KOA patients in addition to those seen with saline solution. The opportunity to further investigate this therapeutic option is questionable. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4532